If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 6 = 2x + 2x Combine like terms: 2 + 6 = 8 8 = 2x + 2x Combine like terms: 2x + 2x = 4x 8 = 4x Solving 8 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + -4x = 4x + -4x Combine like terms: 4x + -4x = 0 8 + -4x = 0 Add '-8' to each side of the equation. 8 + -8 + -4x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -4x = 0 + -8 -4x = 0 + -8 Combine like terms: 0 + -8 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 6(8-7+5)=436 | | 146-4x=6x+16 | | -6x+4=-1-x | | 6x+10=-8-7x | | 0=1+56 | | -8x+2(-3x+4)-5=5-2x | | -53+11y+2=5(3y-3)-4 | | 12y+25=-3 | | x^2+4x=-29 | | 2b-2=19-5b | | 2x^4-26x^2-28=0 | | -7-14y=-8y+5 | | 3(y-1)=2(y-7) | | 2x+6=3x+9-3 | | 69-5x=4x+17 | | 7-8x=43-22x | | 5y-10=0 | | 3b+4.4=2.6 | | 2c-1=-9 | | 4x+6=46-9x | | 4(x+5)=3(x+9) | | 2c+1=-9 | | 3x^4+18=21x^2 | | 3x-2x+10=10-5x-40 | | 3a+5=-1 | | 2+6=x | | 2x^2-5x+7= | | -(4y+4)-(-3y-7)=1 | | 8-7x=-2x+8 | | 33-7x=2x+21 | | 4x=72 | | -27+x=-6 |